Implementasi Algoritma Xtea (Extended Tyni Encryption Algoritma) Dalam Pengamanan Data File Dokumen Teks - Handayani Pandiangan Handayani Pandiangan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
At this time the security of the data stored on the computer is necessary, one of which is to secure the document file can be done is cryptography Cryptography techniques can be used one that can be done is encryption, namely the encryption process before the file is sent and the description is the encryption process after the file is received, so that the process can be kept confidential, and only the person concerned can find out. Confidentiality is a service that is used to maintain information from any party that is not authorized to access it. Thus information can only be accessed by those who have the right to guarantee the security of false information.